Preparation of CaTiO3 Asymmetric Membranes Using Polyetherimide as Binder Polymer - Endang Purwanti Setyaningsih; Maya Machfudzoh; Wahyu Prasetyo Utomo; Hamzah Fansuri (Universitas Gadjah Mada, 2016)
Asymmetric dense and thin membranes have been prepared from powders of perovskite oxide-type CaTiO3 without cracking by phase inversion method. Polyetherimide was used as a polymeric binder in the method. The resulting green membranes, composed of CaTiO3 powder and polyetherimide binder, were sintered at 890, 1100 or 1200 °C. The crystal phase of CaTiO3 was analyzed using X-Ray Diffraction (XRD). The XRD pattern of the synthesized CaTiO3 powder was matched with the reference indicating the formation of CaTiO3 structure. Sintering at 890 °C fails to form a strong membrane. Scanning Electron Microscope (SEM) images of the membranes showed that the membrane had the asymmetric structure with dense layer on one side and porous layer on the other side. The pores in the porous layer were both finger-like and sponge-like structure. The mechanical strength of the membranes, which were determined by Vickers micro hardness method, varied from 3.5 to 25.8 Hv. The strongest membrane without any crack was resulted from sintering at 1200°C with hardness values between 19.4 and 25.8 Hv. Thermal expansion coefficients of the asymmetric membranes sintered at 1100 and 1200 °C, measured with Thermomechanical Analyzer (TMA), were 10.82 × 10-6 and 12.78 × 10-6.C-1 respectively.